Online science learning best practices and technologies - Downing, Kevin F.; Holtz, Jennifer K.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book reviews trends and efforts in web-based science instruction and evaluates contemporary philosophies and pedagogies of online science instruction. This title on an emergent and vital area of education clearly demonstrates how to enrich the academic character and quality of web-based science instruction"--Provided by publisher.
Section V: Best Practice Model for Online Science Learning -- 13. A Didactic Model for the Development of Effective Online Science Courses -- About the Authors -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 13, 2010).
Keywords: Science -- Study and teaching (Higher); Web-based instruction; Education -- Computer network resources; Education, Higher -- Computer-assisted instruction; Education, Higher -- Effect of technological innovations on; Electronic books